HUBUNGAN DIASTASIS RECTI ABDOMINIS DENGAN NYERI PUNGGUNG BAWAH PADA IBU HAMIL - Ulfah, Mariah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
During pregnancy, relaxation of the pelvic joints may happen due to hormonal changes. In line with the gradual weight gain during pregnancy and redistribution of concentration are hormonal influences on the structure of the ligament. Both of these factors alter the posture of pregnant women. This leads to a tendency for the muscle to shorten if stretched abdominal muscles that can lead to muscle imbalance around the pelvis, and the additional voltage can be felt above the ligament. As a result of back pain that usually comes from the sacroiliac or lumbar, and can be a long-term back problems if the balance of muscle and pelvic stability is not restored after delivery. So the authors are interested in examining the relationship diastasis recti abdominis with lower back pain in pregnant women. Objective: to know the description of the characteristics of pregnant women? Knowing diastasis recti abdominis picture in pregnant women? Knowing picture lower back in pregnant women? Knowing the relationship diastasis with low back pain?this research is quantitative research with survey method in pregnant women in the third trimester banjarnegara hospital in june to august 2011. Methode : this type of research is a cross-sectional method with associative testing approach that is conjecture about the relationship between variables in a population that is about the relationship diastasis recti abdominis with low back pain. Keywords: diastasis recti abdominis, pregnancy, lower back pain